The Effect of Inflation on Profitability of Private Commercial Banks (Case Study Of Bank Audi Syria BASY) (Journal of Hama University, 2020)
The objective of this study was to identify the effect of inflation on the profitability of private commercial banks and to determine whether there is a statistically significant relationship between the rate of inflation and the profitability of the bank (return on equity and return on assets). The descriptive analytical methodology and statistical methods were used to achieve the objectives of the study and to analyze and interpret the data to reach conclusions and recommendations, and to was used test the hypotheses the package of programs EXCEL and SPSS, considering that the inflation rate is the independent variable and the profitability of the bank Ownership and Return on Assets (ROE) are the dependent variable The results of the statistical analysis and the hypothesis test showed a statistically significant effect of inflation The profitability of private commercial banks (sample study), has been a set of proposals, the most important of which is that each bank must have a specific entity to follow up the implementation of the policy and objectives of profitability, and the general management of the bank to ensure that the issue of profitability is managed effectively.